ASSESSMENT OF THE STATE AND DEVELOPMENT PROSPECTS OF THE DRY MIX MORTAR MARKET IN UKRAINE AND IN THE WORLD - Романенко, Олеся; Калантир, Діана (Modern engineering and innovative technologies, 2023)
The article is devoted to the assessment of the current state and prospects for the development of the market of Dry Mix Mortar both in Ukraine and in the global context. Information is provided on the actual size of the world market of Dry Mix Mortar fo